Perceived Hindering Factors of Exclusive Breastfeeding among Lactating Mothers of Itahari - Pradhan, Rita; Karn, Basant Kumar; Chaudhary, Ramanand; Yadav, Upendra; Bhandari, Sunita (Journal of College of Medical Sciences-Nepal, 2022)
Introduction: World Health Organization recommends first 6 months of exclusive breastfeeding after birth. It helps in proper growth and development of child. At the same time, it reduces infant mortality by preventing common childhood illnesses and helps for a quicker recovery during illness. So, the study aimed to identify the perceived hindering factors of exclusive breastfeeding among lactating mothers. Methods: A community-based, descriptive cross-sectional study was conducted in Itahari Sub-Metropolitan City. Convenience sampling technique was used to select a total of 123 lactating mothers having infants 0-6 months. A pretested questionnaire was used to interview mothers. Collected data were analyzed using descriptive and inferential statistics. Results: Although nearly all mothers (97.6%) had knowledge about exclusive breastfeeding and 93.5% of them had correct knowledge of recommended duration of EBF, the prevalence of exclusive breastfeeding was only 17.6%. Breastfeeding was initiated within 1 hour by 68.3% of mothers. Half of the mothers perceived that only mother’s milk is not sufficient to their child and about 22% of the mother’s perceived that their child is thirsty and should give water to the infant. Ethnicity and EBF duration to first child in multiparous mother was significantly associated with exclusive breastfeeding practice. Conclusions: Majority of the mothers do not practice EBF although they had known the recommended duration. The major hindering factor of EBF was the perception of the mother that the mother’s breastmilk only is not sufficient to the infant.